MAKE A MATCH LEARNING MODEL TO IMPROVE SOCIAL STUDIES LEARNING OUTCOMES OF CLASS V STUDENTS OF SD KARTIKA XIII-1 AMBON - Damayanti, Aprilia Dewi Putri; Ritiauw, Samuel Patra; Mahananingtyas, Elsinora (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
The aim of this study research is to determine the application of the Make a Match type cooperative learning model to improve social studies learning outcomes regarding geographical conditions in Indonesia for class V students at SD Kartika XIII-1 Ambon. This research use a type of classroom action research. Researcher conducted an initial test to obtain information on the extent of student abilities in mastering the learning material. The average score of students initial test results was 33, 37%. This shows that class V students at SD Kartika XIII-1 Ambon have not yet reached the specified minimum completeness criteria (KKM). In general, the average class score for student in cycle I was 53, 38% and the average for the final test in cycle test was 81, 75%. The application of make a match type cooperative learning model to improve student cognitive learning outcomes has shown an increase in each cycle. This can be seen from the level of student in improving learning outcomes through tests given at the end of each cycle.